The clinical, functional, and radiological effect of long-term used immunosuppressive therapy for post-COVID-19 interstitial lung disease : Immunosuppressive therapy in post-COVID-19-ILD - Gul, Sule; Demirkol, Barış; Eren, Ramazan; Baydili, Kursad Nuri; Babaoğlu Elkhatroushi, Burcu; Ulusan, Şerife Nur; İlhan, Umut; Çörtük, Mustafa; Çetinkaya, Erdoğan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Persistent interstitial lung disease (ILD) after COVID-19 infection can lead to severe loss of respiratory function and a decrease in the quality of life. There is no consensus regarding the treatment of post-COVID-19-ILD. This study aims to investigate the effectiveness of immunosuppressive treatment for this group of patients. Methods: This retrospective observational study included patients diagnosed with post-COVID-19-ILD from 2021 to 2022. Patients who had pulmonary symptoms, required prolonged oxygen therapy, and/or had restrictive pulmonary function test (PFT) and/or DLCO